Extracting the Forest Type From Remote Sensing Images by Random Forest - Linhui, Li; Weipeng, Jing; Huihui, Wang (IEEE sensors journal, 2021)
Identifying the types of forest and the corresponding distribution is of significance in forest resource monitoring and management. Considering the low accuracy of extracting the information of forest types from high-resolution remote sensing images and the lack of an effective identification method. The GF-2 remote sensing image in the Laoshan construction area of the Maoershan Forest Farm, Heilongjiang Province was as the data source, supplemented by aerial RGB images with a resolution of 0.2 m and the second type inventory of forest resources data. Considering the spatial characteristics of the spectrum, texture, vegetation index, terrain, multiscale segmentation was performed, the optimal feature space was constructed, and the number of decision trees was estimated. In this manner, an object-oriented random forest (RF) scheme was established. Comparative experiments were performed using the support vector machine(SVM) classifier. The experimental results indicated that the overall accuracy and kappa coefficient of the proposed method was 83.16% and 79.86%, respectively, higher than those of the SVM classification method. These findings demonstrated that the proposed method can effectively increase the classification accuracy of forest types.